Método de medição sem contato e reconstrução 3D a partir do foco utilizando processamento e análise de imagens - Barbosa, Jonathas Jeronimo (2012)
The massive use of mills and hydrocyclones operating in closed circuit, in several great relevance socio-economic industrial applications, checks special importance to the problem of the development of processes and mathematical models returned to the optimization of the circuit. This work presents an investigation about about techniques for reducing the prediction error (approximation by spheres) to increase accuracy in non-contact measurements of particle size of minerals in order to increase the effciency of classiffcation by hydrocyclones. Computational methods for counting and measuring particles were developed and implemented, in order to compare the computational vision and particle size separation sieving methods. The proposed method also deals with 3D reconstruction of the particles based on the measurement of their heights. To this goal, a stack of images with variable focus is captured. From this stack calculate the average particle size (estimated from the z axis), display the pictures of the stack through the focus index and the image height. An estimate of the average height of the particles is done and than approximate the shape of the particles (spheroids) and comparison with the results approximating a sphere. Measuring instruments have been adapted for the acquisition of images and also for estimating the height of the particles of the samples.